2021
DOI: 10.26554/sti.2021.6.2.74-84
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Active Chemical Compounds of Honey from Some Regions in Indonesia

Abstract: Bees produce honey from plant nectar, plant secretions, and excretions of plant-sucking insects. Indonesian local honey contains active compounds that have the potential effect as antioxidant and anticancer. The composition and biological effects of honey vary depending on the flower sources; seasonal and environmental factors can also influence the composition and the physical products. This research was conducted to identify the chemical compounds found in several honey samples produced by beekeepers in Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Geographic variations in honey's total phenol and flavonoid contents and antioxidant properties are mainly attributed to differences in the regional plants preferred by bees (Becerril-Sanchez et al, 2021). Sumarlin et al (2021) demonstrated the presence of active chemical compounds in honey from several eastern regions of Indonesia that were sourced from the nectar sources of rambutan and longan. However, Indonesia's wide range of geographic locations, including the islands of Sumatra and Java, contains many botanical sources.…”
Section: Introductionmentioning
confidence: 99%
“…Geographic variations in honey's total phenol and flavonoid contents and antioxidant properties are mainly attributed to differences in the regional plants preferred by bees (Becerril-Sanchez et al, 2021). Sumarlin et al (2021) demonstrated the presence of active chemical compounds in honey from several eastern regions of Indonesia that were sourced from the nectar sources of rambutan and longan. However, Indonesia's wide range of geographic locations, including the islands of Sumatra and Java, contains many botanical sources.…”
Section: Introductionmentioning
confidence: 99%
“…Honey is a natural substance with various bioactivity compounds, including honey produced in Indonesia. For example, Trigona sp honey, Kaliandra, and Kelengkeng have the potential as supplements for lung cancer patients (Sumarlin et al, 2019), and the presence of aurantiamide acetate (antiviral or anti-inflammatory and therapeutic agent for influenza) (Sumarlin et al, 2021). In addition, the ability as an antibacterial has also been widely found.…”
Section: Introductionmentioning
confidence: 99%